Redistribution of the intra-acrosomal EGFP before acrosomal exocytosis in mouse spermatozoa - Hirohashi, Noritaki (2015)
Mammalian spermatozoa must undergo complex physiological and morphological alterations within the female reproductive tract before they become fertilization competent. Two important alterations are capacitation and the acrosome reaction (AR), by which spermatozoa become capable of penetrating the zona pellucida (ZP) of the oocyte. Although various biochemical stimulants have been reported to induce the AR, the true physiological inducer in vivo remains to be identified. Previously, it has been reported that most fertilizing spermatozoa undergo the AR before contacting the ZP and that only a small fraction of in vitro-capacitated spermatozoa can penetrate the ZP. Therefore, it is important to identify which capacitating spermatozoa undergo the AR in response to potential AR inducers such as progesterone. Here we show that spermatozoa undergo a dynamic rearrangement of the acrosome during in vitro capacitation. This involves the rapid movement of an artificially introduced soluble component of the acrosome, enhanced green fluorescent protein (EGFP), from the acrosomal cap region to the equatorial segment (EQ) of the sperm head. Spermatozoa exhibiting the EQ pattern were more sensitive to progesterone than were those without it. We suggest that spermatozoa that are ready to undergo acrosomal exocytosis can be detected by real-time EGFP imaging. This offers a promising new method for identifying where spermatozoa undergo the AR in the female reproductive tract in vivo.